Territorial Differences of Human Development Index in Romania - IBOLYA KURKÓ (Romanian Review of Regional Studies, 2011)
The measuring of human capital, human development from both a quantitative and a qualitative point of view is difficult, the problem being further complicated if we consider regional and territorial approaches as well. At an international level, the Human Development Index is usually used for measuring and comparing these issues. This index addresses the most complex level of development of a region through the aggregation of the three indices from demographic (life expectancy at birth), social (education level) and the economic sphere (GDP per capita) with which we can have a much more complex picture about living standards of the population as well as the development level of a country. Because the applicability of this index has caused serious debates since its introduction, this study also focuses on selecting the right indicators for measuring human development.